On the reversible geodesics of a Finsler space endowed with a special deformed $(α, β)$-metric - Laurian-Ioan Pişcoran; Cătălin Barbu; Ali Akram (AUT Journal of Mathematics and Computing, 2021)
The scope of this paper is twofold. On the one hand, we will investigate the reversible geodesics of a Finsler space endowed with the deformed newly introduced $(α, β)$-metric\begin{equation}F_{ε}(α,β)=\frac{β^{2}+α^{2}(a+1)}{α}+εβ\end{equation}where $ε$ is a real parameter with $|ε|<2\sqrt{a+1}$ and $a\in \left(\frac{1}{4},+∞\right)$; and on the other hand, we will investigate the T-tensor for this metric.